The Portugal situation during the financial crisis - Milena Lopreite (Advances in Management & Applied Economics, 2011)
Today it's frequently used the terms PIGS or PIIGS, acronyms used by economic journalists to refer to different countries of the European Union for their statement of affairs. The bad connotation is evident from the fact that pigs in English suggest the bad state of the economies of these countries. PIGS has been used at the beginning of the years 1990 to indicate four countries of southern Europe: Portugal, Italy, Greece and Spain. Ireland has sometimes been added during the year 2007, so the acronym is modified in PIIGS. Nevertheless, the alarms of BCE about the public accounts of these States it seems to exclude Italy from the group of the countries characterized by very bad statements of affairs. The aim of this work is to analyze especially during the financial crises the situation of the public accounts in Portugal, one of the countries with greater difficulties and probably with the worse condition if we exclude the dramatic Greek case. In Portugal, the economic growth has been superior to the average UE, for big part of the decade 1990-2001, even if the remains under the 75% of the principal European economies' PIL.
Keywords: E32; E60; H60; 330; business; PIL; economic growth; debts; risk